The Influence of Beauty Vlogger as A Marketing Influencer, Brand Trust and Brand Image on The Decision to Purchase Ms Glow Beauty Product in The Shopee Marketplace - Irawan, Muhammad Rizal Nur (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2023)
This research aims to determine how Powerhouse Advertising, Brand Trust, and Brand Picture influence Purchase Choices to some extent—this type of quantitative descriptive research. Respondents are Shopee users of the Faculty of Economics, Lamongan Islamic University. Purposive sampling was used to select samples. The results showed that simultaneously, beauty vloggers had a significant effect on Brand Trust Purchase Decisions, the most dominant influence on MS Glow Beauty Product Purchase Decisions in the Shopee Marketplace.